(untitled) (Journal of Student Affairs in Africa, 2021)
Higher education institutions, including medical schools, still grapple with the challenge of poor academic performance of students. Some studies report the positive results of providing academic guidance for common challenges such as poor and/or ineffective time management, study methods, test- and exam-taking techniques and management, and the high academic workload of undergraduate medical students. However, limited detailed insights and understanding of medical students who experience more complex challenges are available. This study was conducted at a medical school in South Africa to determine undergraduate medical students’ perceptions of factors affecting their academic performance. A total of 89 semi-structured interviews were held with undergraduate medical students who were identified as having academic problems between 2012 and 2015. According to the results, more blacks, males and first- and secondyear students experienced poor academic performance. Prominent findings included the harsh realities and implications of lack of accommodation for black students; how poor academic performance can lead to an array of other social and psychological problems, such as withdrawal of bursaries and negative achievement emotions that some students experience. Compared to the usual objective measures of individual ability, the rich qualitative data of cases presented in this study reveal critical, real insights and understanding of students’ challenges from their own perspective.